‘His Best Part Lies Hidden in His Learned Heart’: Aernout van Buchell’s Alba Amicorum - Schlueter, June (Early Modern Low Countries, 2022)
This article proposes that the historian Aernout van Buchell was a cultural go-between, quietly engaged in a transnational project of globalization. The young van Buchell’s first album amicorum, begun in 1584, reveals an intellectually restless young man who was given to depression and even attempted suicide but who discovered the study of antiquities on his year-long stay in Paris. His second album reveals an older, settled, purposeful historian whose album friends were scholars and artists of considerable reputation. At least since his year in Paris, van Buchell was committed to obliterating the boundaries of space and time and removing the intellectual limits of his mind. As with the antiquities he studied, van Buchell’s alba endorse a common heritage and offer to posterity the wisdom of the ancients and that of the many contributors to his album. His stance was that of a humanist, which, in the early modern period, entailed a revival of classical languages, literature, and moral precepts.